Fotografi Di Era Media Sosial : Studi â€œToko Memorabiliaâ€ Karya Agan Harahap - Purnomo, Aji Susanto Anom (Institut Bisnis dan Teknologi Indonesia, 2018)
The development of photography technology in the era of social media currently contribute various problems that need to be studied and reflected. One of them is about the essence or meaning of the presence of